Penguasaan Nahwu Menggunakan Kitab Nazm Al-‘Imrithi Dan Kemampuan Membaca Kitab Kuning: Studi Analisis Korelasional - Muyasiroh, Wildatul (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2024)
This research aims to determine the relationship between mastery of nahwu using the Nazm Al-'Imrithi book and the ability to read the yellow book (Kitab Kuning). The research was carried out on a population of class XI students at MA Roudlotul Mubtadiin Balekambang. The research uses quantitative methods, where primary data is obtained through tests. The sample consisted of 30 students from a total population of 62 students obtained using the Purposive Sampling method. Researchers collected data originating from test instruments, interviews and documentation. The research results revealed that the implementation of nahwu learning using the book Nazm Al-'Imrithi was at a percentage level of 79.93%, which means it was